Dive into the world of knowledge and get your queries resolved at IDNLearn.com. Discover prompt and accurate responses from our experts, ensuring you get the information you need quickly.
Sagot :
Answer:
[tex]a = 1[/tex]
[tex]b = 1[/tex]
[tex]c = 0[/tex]
Explanation:
Given
The above code segment
Required
The final values of [tex]a,\ b\ \&\ c[/tex]
The following line declares and initializes the values of a, b and c
int a = 1; int b = 0; int c = -1;
So, we have:
[tex]a = 1; b =0; c = -1[/tex]
Next, the following if condition is tested
if ((b + 1) == a)
[tex]b + 1 =0 +1[/tex]
[tex]b + 1 = 1[/tex]
And:
[tex]a = 1[/tex]
So,
[tex]b + 1 = a = 1[/tex]
Since the condition is true, the statements in the curly brace { } will be executed;
[tex]b++ \to b = b+1 \to b = 0 + 1 \to b = 1[/tex]
So:
[tex]b = 1[/tex]
[tex]c += b \to c = c+b \to c = -1 + 1 \to c = 0[/tex]
So:
[tex]c = 0[/tex]
Next, the following if condition is tested
c == a
c = 0 and a =1
So:
[tex]c \ne a[/tex]
That means, the statements in its curly brace will not be executed.
So, the final values of a, b and c are:
[tex]a = 1[/tex]
[tex]b = 1[/tex]
[tex]c = 0[/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Your questions find clarity at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.